Running the LogiQL REPL - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
The lb command is not the only way to access the LogiQL runtime engine. You can also use the interactive REPL (read-eval-print loop). REPLs exist for many languages and provide an easy-to-use means of learning a language, getting answers to modest language questions, and trying small experiments. As the name REPL indicates, a REPL works by repeatedly taking the following three steps: read in a user request, evaluate its effect on the workspace, and print the results. The commands that it accepts are the same that you can give to the lb including addblock, exec, list, print, and query.